ANALISIS HUBUNGAN ANTARA PERTUMBUHAN PENDUDUK, KONSUMSI MAKANAN, DAN TINGKAT PARTISPASI ANGKATAN KERJA PEREMPUAN TERHADAP PERTUMBUHAN EKONOMI DI KOTA MAGELANG - Yuyun Guna Winarti (Jendela Inovasi Daerah, 2020)
Economic growth is a measure of people's welfare. This indicator reflects the extent of economic activities of population that gives additional income for them. The income encourages people to increase consumption and savings. Today, there is a different consumption pattern in Magelang City. Food consumption is smaller than non-food consumption. On the other hand, food and beverage consumption (cooked food and beverage ready for consumption) is the most dominant. One cause of this phenomenon is working women increasing. This paper wants to find the relationship between population growth, food consumption, and the women labor force participation rate for economic growth in Magelang City. The secondary data from Statistics Indonesia-BPS are used. The analysis showed that partially population growth, food consumption, and the women labor force participation rate had positive and significant effects on economic growth. But the effect does not occur simultaneously.